FINANCIAL INSURANCE FOR ENTERPRISES – ANALYSIS OF DEMAND AND SUPPLY - Wicka, Aleksandra (Management and Administration Journal, 2020)
The aim of the article is to assess changes in the enterprises’ demand for financial insurance. The analysis covered expenses incurred by business entities on purchase thereof and supply by the entity. Data used in the study came from secondary sources published in studies by the Polish Financial Supervision Authority (KNF), the Polish Chamber of Insurance (PIU) and the Central Statistical Office (GUS). Furthermore, information from the studies-related literature has been included. The time period of studies covered the years 2005–2018. Selected types of insurance included in financial insurance have been presented herein and industries which these products are especially targeted at have been indicated. Moreover, supply by entities has been discussed with an indication of insurers who hold a leading position in the financial insurance sales in Poland. It has been stated that the demand (by value) for financial insurance in the years 2005–2018 was growing. The amount of the gross premium written in 2018 was twice as high as in 2005 and amounted to PLN 1.09 billion. Furthermore, it has been determined that the highest average dynamics of market growth concerned insurance from various financial risks (group 16), which are usually offered jointly with other insurance products, but also the dynamics of expenses incurred on purchasing surety was over 200%, whereas, in 2018 it was even 360%.